Estrutura genética populacional de Prochilodus costatus Valenciennes 1850 (Characiformes, Prochilodontidae) no Alto São Francisco - Silva, Alline Braga (2011)
Studies of population structuring are important tools for the conservation of species and can assist in decisions for the creation, management and restructuring of conservation units. Recent researches conducted with freshwater migratory fish have demonstrated the organization of metapopulations in species of the genus Prochilodus and Brycon, suggesting that the tributaries where the individuals reproduce have a key role in this structuring. Furthermore, the homing behavior, characterized by the return of individuals to their birthplace to breed, has been reported for the genus Prochilodus. This behavior restricts gene flow, which can lead to population structuring. Moreover, a previous study in Prochilodus costatus was not able to detect population structuring when comparing three sites downstream the dam of Três Marias (MG). However, the idea that tributaries may contain different genetic populations remains to be tested. In this context, we investigated the population genetic structure of P. costatus in the region of the headwaters of the São Francisco river, where the extension of the protected area Parque Nacional da Serra da Canastra is discussed. We used ten microsatellite loci to conduct the studies in three tributaries of the Upper São Francisco. We use the fixation index (FST) and AMOVA to verify the genetic differentiation between subpopulations previously defined and assignment tests to see how many people there. The results showed a high diversity within subpopulations, low diversity among subpopulations and the existence of only one population group. Thus, the conservation policies for this species should consider a high variability in a single and large population model.